Cannabis use and associated psychiatric morbidities among psychiatric outpatients of a teaching institute in Eastern Nepal (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Cannabis is one of the most widely used psychoactive substances worldwide and has been linked to various psychiatric disorders. Despite its traditional use in Nepal, data on cannabis use among psychiatric outpatients are limited. This study aimed to find out the patterns of cannabis use and to determine its associated socio-demographic factors and comorbid psychiatric disorders among psychiatric outpatients attending a tertiary care teaching hospital in Eastern Nepal.Methods and materials: A hospital-based cross-sectional study was conducted among 500 psychiatric outpatients at BPKIHS, Dharan. Socio-demographic data were collected using a semi-structured proforma. Cannabis use was assessed with the Cannabis Use Disorders Identification Test–Revised (CUDIT-R), and psychiatric diagnoses were made using ICD-10 criteria. Associations between cannabis use and socio-demographic and psychiatric variables were analyzed using Chi-square and Fisher’s exact tests Results: Ever cannabis use was reported by 38(7.6%) patients and 25(5%) patients were current users. Hazardous use and possible cannabis use disorder were observed in 8 patients (1.6%), and 15 patients (3%) respectively. Lifetime cannabis dependence was present in 16 (3.2%) patients. Cannabis use was significantly associated with young age 16–25 years (p